Brainstem Pain-Modulation Circuitry and Its Plasticity in Neuropathic Pain: Insights From Human Brain Imaging Investigations - Mills, Emily P.; Keay, Kevin A.; Henderson, Luke A. (Frontiers in Pain Research, 2021)
Acute pain serves as a protective mechanism that alerts us to potential tissue damage and drives a behavioural response that removes us from danger. The neural circuitry critical for mounting this behavioural response is situated within the brainstem and is also crucial for producing analgesic and hyperalgesic responses. In particular, the periaqueductal grey, rostral ventromedial medulla, locus coeruleus and subnucleus reticularis dorsalis are important structures that directly or indirectly modulate nociceptive transmission at the primary nociceptive synapse. Substantial evidence from experimental animal studies suggests that plasticity within this system contributes to the initiation and/or maintenance of chronic neuropathic pain, and may even predispose individuals to developing chronic pain. Indeed, overwhelming evidence indicates that plasticity within this circuitry favours pro-nociception at the primary synapse in neuropathic pain conditions, a process that ultimately contributes to a hyperalgesic state. Although experimental animal investigations have been crucial in our understanding of the anatomy and function of the brainstem pain-modulation circuitry, it is vital to understand this system in acute and chronic pain states in humans so that more effective treatments can be developed. Recent functional MRI studies have identified a key role of this system during various analgesic and hyperalgesic responses including placebo analgesia, offset analgesia, attentional analgesia, conditioned pain modulation, central sensitisation and temporal summation. Moreover, recent MRI investigations have begun to explore brainstem pain-modulation circuitry plasticity in chronic neuropathic pain conditions and have identified altered grey matter volumes and functioning throughout the circuitry. Considering the findings from animal investigations, it is likely that these changes reflect a shift towards pro-nociception that ultimately contributes to the maintenance of neuropathic pain. The purpose of this review is to provide an overview of the human brain imaging investigations that have improved our understanding of the pain-modulation system in acute pain states and in neuropathic conditions. Our interpretation of the findings from these studies is often guided by the existing body of experimental animal literature, in addition to evidence from psychophysical investigations. Overall, understanding the plasticity of this system in human neuropathic pain conditions alongside the existing experimental animal literature will ultimately improve treatment options.